Detection of Wuchereria bancrofti in the city of São Luís, state of Maranhão, Brazil: New incursion or persisting problem? - Tatiane Alexandre de Araújo; Alessandra Lima de Albuquerque; Danielle Cristina Tenório Varjal de Melo; Eloína Maria de Mendonça Santos; André Luiz Sá de Oliveira; Constância Flávia Junqueira Ayres; Cláudia Maria Fontes de Oliveira (PLoS Neglected Tropical Diseases, 2023)
Background The elimination of lymphatic filariasis (LF) from Brazil by 2020 was not accomplished; however, this goal can be achieved in the upcoming years with the assistance of specific strategies. The surveillance of LF can be performed using molecular xenomonitoring (MX), a noninvasive method used to infer the presence of the parasite in the human population. Herein, São Luís (state of Maranhão) was the first city to be investigated to identify whether LF transmission in Brazil has been interrupted and if there were any new incursions. Methodology/principal findings Mosquitoes were collected by aspiration at 901 points distributed among 11 neighborhoods in São Luís with records of patients with microfilaremia. Pools of engorged or gravid Culex quinquefasciatus females were evaluated by WbCx duplex PCR with endogenous control for mosquitoes and target for W. bancrofti for determining the vector infection rate. Among the 10,428 collected mosquitoes, the most abundant species were C. quinquefasciatus (85%) and Aedes aegypti (12%). Significantly larger numbers of mosquitoes were collected from the neighborhoods of Areinha and Coreia (p<0.05). MX performed using PCR validated 705 pools of engorged or gravid females, fifteen of which were positive for Wuchereria bancrofti in two neighborhoods. Conclusions The high density of engorged C. quinquefasciatus females per home, inadequate sanitation, and detection of W. bancrofti-infected mosquitoes in the city of São Luís represent a warning of the possible upsurge of LF, a disease that is still neglected; this underscores the need for the ostensive monitoring of LF in Brazil.